# Given the function f(x) = 6 (x + 2) - 3, solve for the inverse function when x = 21.

**Solution:**

It is given that

f(x) = 6 (x + 2) - 3

It can be written as

f(x) = 6x + 12 - 3

f(x) = 6x + 9

In order to find the inverse,

consider y = f(x)

y = 6x + 9

Let us interchange x and y,

x = 6y + 9

By solving for y,

x - 9 = 6y

Divide both sides by 6,

x/6 - 9/6 = y

So we get

y = 1/6 x - 3/2

So the inverse function f^{-1 }(x) = 1/6 x - 3/2

When x = 21

f^{-1 }(21) = 1/6 (21) - 3/2

Taking LCM

f^{-1 }(21) = 21/6 - 3/2

f^{-1 }(21) = (42 - 18)/12

f^{-1 }(21) = 24/12

f^{-1 }(21) = 2

Therefore, the inverse function when x = 21 is 2.

## Given the function f(x) = 6 (x + 2) - 3, solve for the inverse function when x = 21.

**Summary:**

The inverse function f(x) = 6 (x + 2) - 3 when x = 21 is 2.

Math worksheets and

visual curriculum

visual curriculum